Relationship of modifiable risk factors with the incidence of thyroid cancer: a worldwide study - Zahra Maleki; Jafar Hassanzadeh; Haleh Ghaem (BMC Research Notes)
Abstract Background Thyroid cancer is one of the most common cancers of the endocrine system. The incidence of this cancer has increased in many countries. Many cases of thyroid cancer do not have any symptoms. This cancer has different risk factors. Some of them are unchangeable and some can be changed and modified. So, it is necessary to identify these risk factors. Therefore, this global study was conducted for the first time to investigate the correlation between the age-standardized incidence rate of thyroid cancer (ASIR) and some modifiable risk factors worldwide. Methods The data of this global ecological research has been collected on the official website of health data ( https://www.healthdata.org/ ) for 204 countries and territories from 1990 to 2019. Pearson correlation coefficient was used to evaluate the correlation. Finally, statistical modeling was done using Generalized Additive Model (GAM). Statistical analyzes were performed using R version 4.2.2 software. Results ASIR of thyroid cancer has a positive and significant correlation with tobacco, Secondhand smoke (SHS), mean BMI, and low physical activity. Multiple GAM showed that gender, alcohol consumption, smoking, SHS, mean BMI, and low physical activity have a statistically significant relationship with the ASIR of thyroid cancer (All Relative Risk > 1). Conclusion This study showed that the risk of thyroid cancer is higher in women than men. Smoking, alcohol, obesity, and low physical activity may be risk factors for ASIR of thyroid cancer. Also, this study, for the first time globally, hypothesized an association between exposure to secondhand smoke and ASIR of thyroid cancer. To prevent and accurately control thyroid cancer, there is a need to increase awareness about the modifiable risk factors of this cancer.